The QFHSA Supports Bill S-251 : An Act to Repeal Section 43 of the Criminal Code (Truth and Reconcilliation Commission of Canada's Call to Action Number 6) - Quebec Federation of Home and School Associations (QFHSA) (2023)

Faits saillants : Enquête sur la vulnérabilité des pères d'expression anglaise - Community Health and Social Services Network (CHSSN) (2022)

Survey Highlights on the Vulnerability of English-speaking Fathers - Community Health and Social Services Network (CHSSN) (2022)

Gun Violence in Montréal : Context, Causes, Reactions, and Recommendations - Pettem, Alexandre (Youth for Youth Québec (Y4Y Québec), 2021)
Montréal has recently been experiencing an unprecedented spike in gun violence, primarily perpetrated by a younger demographic. These shootings are occurring more frequently in broad daylight, in the midst of populated urban areas (Magder). As of August 31, the Montréal police (the SPVM) had documented 77 separate firearms being discharged, with 360 bullets being fired in roughly 100 shootings. This has already surpassed total instances for 2019 and 2020. 654 firearms have been seized, furthermore, the highest ever for the SPVM. This has led to 23 homicides, which is already rapidly approaching the 25 that were observed in both 2019 and 2020 (Perron).

QCGN Statement on Murder of Muslim Family in London, Ontario : Human Rights and Freedoms Are Not to be Taken for Granted - Quebec Community Groups Network (QCGN) (2021)

Restraints : Information for Clients and Families / Mesures de contrôle : Publications aux usagers et aux proches - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Brief Addressed to the Committee on Culture and Education and Bill 56 : An Act to Prevent and Deal with Bullying and Violence in Schools - Quebec Federation of Home and School Associations (QFHSA) (2012)
The Quebec Federation of Home and School Associations (QFHSA) welcomes the opportunity to comment on Bill 56, An Act to prevent and deal with bullying and violence in schools.

Un mémoire à l'intention de la Commission de la culture et de l’éducation : portant sur le projet de loi no 56 : Loi visant à lutter contre l’intimidation et la violence à l’école - Quebec Federation of Home and School Associations (QFHSA) (2012)
La Fédération Québécoise des Associations Foyers-Écoles (FQAFÉ) accueille l’opportunité de pouvoir commenter le projet de loi 56, intitulé Loi visant à lutter contre l’intimidation et la violence à l’école.

Black Communities Speak Out About Violence - Tichit, Laurence; Jaccoud, Mylène (Black Community Resource Centre (BCRC), 2009)
This project was an initiative of six Black community organizations in Montreal concerned with the problem of violence. It was designed to unfold in three consecutive phases: 1) establish a subject overview by conducting focus groups with members of Montreal's Black communities, 2) organize a roundtable discussion with key people involved in the issue, and 3) develop an intervention plan. This report examines each of these phases which were aimed at defining the bases for mobilization and presenting possible strategies to address the issue of violence within the Black communities.

Semaji - Black Community Resource Centre (BCRC) (2008)

Open and Public Inquiry into the Death of Mr. Rohan Wilson - Alliance Quebec (AQ) (2004)

"Hate is Hate" - Alliance Quebec (AQ) (2003)

Press Conference - Alliance Quebec (AQ) (2002)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1991)